2008
DOI: 10.1007/s00726-008-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of muscle protein degradation, not synthesis, by dietary leucine in rats fed a protein-deficient diet

Abstract: The aim of this study was to elucidate the effects of long-term intake of leucine in dietary protein malnutrition on muscle protein synthesis and degradation. A reduction in muscle mass was suppressed by leucine-supplementation (1.5% leucine) in rats fed protein-free diet for 7 days. Furthermore, the rate of muscle protein degradation was decreased without an increase in muscle protein synthesis. In addition, to elucidate the mechanism involved in the suppressive effect of leucine, we measured the activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 37 publications
2
41
1
7
Order By: Relevance
“…Many studies have shown that various catabolic conditions activate the ubiquitin-proteasomal pathway (30,31). We have previously shown that dietary Leu intake suppresses myofibrillar proteolysis by inhibiting the autophagiclysosomal pathway (13). Ogata et al (32) demonstrated that the ratio of LC3-II/LC3-I, a marker of the autophagic-lysosomal pathway activity, increased in a fasting duration-dependent manner.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Many studies have shown that various catabolic conditions activate the ubiquitin-proteasomal pathway (30,31). We have previously shown that dietary Leu intake suppresses myofibrillar proteolysis by inhibiting the autophagiclysosomal pathway (13). Ogata et al (32) demonstrated that the ratio of LC3-II/LC3-I, a marker of the autophagic-lysosomal pathway activity, increased in a fasting duration-dependent manner.…”
Section: Discussionmentioning
confidence: 92%
“…We have reported that supplementation with Leu under a protein-deficient diet suppresses myofibrillar protein degradation in rats (11,12). We reported that the suppression effect of Leu occurred by inhibition of the autophagic-lysosomal pathway, a proteolytic system (13). Thus, Leu also regulates muscle protein degradation.…”
mentioning
confidence: 96%
“…In chick skeletal muscle, leucine decreased MPB in association with decreased ubiquitin and 20S proteasome C2 subunit mRNA expression (11). However, a study in rat skeletal muscle reported no change in proteasome mRNA expression or expression of E3 ubiquitin-ligases muscle atrophy F-box (MAFbx, also known as atrogin-1) and Muscle RING Finger 1 (MuRF1), but a decrease in autophagy marker microtubule-associated protein 1 light chain 3 (LC3) B-II expression (22). Overall, verification of the effects of leucine on MPB pathways with concurrent measures of muscle protein turnover in humans is lacking.…”
Section: Introductionmentioning
confidence: 96%
“…Although ingestion of essential AA has been reported to have no effect on protein breakdown (43), other studies have shown a reduction in protein degradation with branched-chain AA or leucine administration (44,48,49,53,54,66). It has been reported that branched-chain AA and leucine modulate the ubiquitin-proteasome system by regulating MAFbx/ atrogin-1 and MuRF-1 mRNA levels (4,7,38,49) and the autophagy-lysosome system through alterations in the expression of LC3II (66), although evidence to the contrary has also been reported (49). In this study, LEU infusion during CON feeding did not have any effect on the ubiquitin-proteasome system, as indicated by the lack of change in the phosphorylation of FoxO3 and in the abundance of atrogin-1 and MuRF-1.…”
Section: E628mentioning
confidence: 99%